Toxin : the cunning of bacterial poisons - Lax, Alistair J., 1953- (OUP E-Books., 2005)
Alistair Lax takes a fascinating look at these most devious molecules, explaining the many ingenious mechanisms they use to penetrate our cell's defences, and the deadly pandemics that result. A story not only of disease but also of human rivalry and persistence in our struggle to understand, combat, and harness these powerful toxins. - ;What do the following have in common: the promise of Botox as the key to everlasting youthful looks; E. coli O157 hamburger disease; a mysterious illness which killed 35 heroin users in 2000; and the assassination by poisoned umbrella-tip of a Bulgarian dissid.